08.15 Stability of infliximab under different storage conditions used as a standard for in-house infliximab elisa. (1st March 2017) - Ogrič, Manca; Žigon, Polona; Praprotnik, Sonja; Drobne, David; Štabuc, Borut; Tomšič, Matija; Sodin-Semrl, Snezna; Čučnik, Saša
Abstract : Background: Infliximab (IFX) is a therapeutic chimeric monoclonal antibody targeting tumour necrosis factor-alpha (TNF-α) used for treating chronic inflammatory diseases, such as Crohn`s disease, ulcerative colitis, spondyloarthritis and rheumatoid arthritis. Assessing IFX serum levels is recommended to optimally evaluate patient's response to therapy using well-selected methodology. Our in-house IFX ELISA proved to be highly comparable to commercially available apDia (r=0.925, p<0.001) and Promonitor kits (r=0.943, p<0.001), with 100% agreement between in-house IFX ELISA and both kits. In the current study we aimed to examine the stability of the original IFX medication (Remicade) and its biosimilar (Remsima) under different storage conditions, for later use as standard in our in-house IFX ELISA. Materials and methods: Lyophilized Remicade and Remsima were reconstituted to a final concentration of 12 µg/mL in: a) sterile water stored at 4°C, b) phosphate buffered saline with 1% bovine serum albumin (1% BSA/PBS) and c) 1% BSA/PBS with 25% glycerol, both stored at −20°C. In-house IFX ELISA, using the differently stored standards, was performed at days 0, 2, 7, 35, 93 and 180 after first reconstitution. Briefly, high binding microtiter plates were coated overnight at 4°C with TNF-α. After washing and blocking with 1% BSA/PBS, followed by an additional wash, samples and standards were applied and incubated for 2 hour at 37°C. The binding was detected with an alkaline phosphatase-conjugated anti-IgG antibody. Results: Measured IFX concentrations in different time points were most consistent for Remsima stored in 1% BSA/PBS at −20°C (12.14±0.44 µg/mL, with coefficient of variation (CV) 3.7%) or 1% BSA/PBS with 25% glycerol (12.15±0.45 µg/mL, CV 3.7%). Under these conditions IFX concentrations determined at different time points, differed from actual 12 µg/mL concentration, on average for 0.15 µg/mL (range 11.52–12.79 µg/ml). Remicade stored either in water, 1% BSA/PBS or 1% BSA/PBS with 25% glycerol yielded less repeatable results with standard deviation 0.67–1.30 µg/mL and CV 6.3%–10.9%. Conclusions: Remsima stored in either 1% BSA/PBS or 1% BSA/PBS with 25% glycerol at −20°C proved to be the most stable standard solution for use in our in-house IFX ELISA.